2011
DOI: 10.1093/eurheartj/ehr269
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of persistent atrial fibrillation by genetic knockdown of caspase 3: a pre-clinical pilot study

Abstract: Knockdown of caspase 3 by atrial Ad-siRNA-Cas3 gene transfer suppresses or delays the onset of persistent AF by reduction in apoptosis and prevention of intra-atrial conduction delay in a porcine model. These results highlight the significance of apoptosis in the pathophysiology of AF and demonstrate short-term efficacy of gene therapy for suppression of AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 40 publications
4
76
1
1
Order By: Relevance
“…Ventricular cell loss has been confirmed in AF patients with tachycardia-induced cardiomyopathy (15,16). However, in the present study, myocardial injury was confirmed in the CHF-AF patients, irrespective of whether the heart rate was strictly controlled.…”
Section: Mechanisms Of Myocardial Damage In Af Patientscontrasting
confidence: 57%
“…Ventricular cell loss has been confirmed in AF patients with tachycardia-induced cardiomyopathy (15,16). However, in the present study, myocardial injury was confirmed in the CHF-AF patients, irrespective of whether the heart rate was strictly controlled.…”
Section: Mechanisms Of Myocardial Damage In Af Patientscontrasting
confidence: 57%
“…Cells were cultured in supplemented Claycomb medium (JRH Biosciences, Lenexa, KS, USA) as previously described [36,37].…”
Section: Hl-1 Cell Culturementioning
confidence: 99%
“…Cells were cultured and maintained in Claycomb medium, supplemented with 10% FBS, 1% norepinephrine (Sigma-Aldrich, Steinheim, Germany), 2 mM L-glutamine, 100 U mL -1 penicillin G sodium and 100 mg mL -1 streptomycin sulphate (G418; Gibco BRL) as described (Claycomb et al, 1998;Lugenbiel et al, 2012;Trappe et al, 2012). Drug treatment was performed when cells were 80% confluent.…”
Section: Cell Culturementioning
confidence: 99%